African spirituality, politics and knowledge systems: sacred words and Holy realms - Falola, Toyin (Bloomsbury Studies in Black Religion and Cultures, 2022)
"Focusing on the three leading religious traditions in Africa (African Traditional Religion, Islam, and Christianity), this book shows how belief in the supremacy of sacred words compels actions and influences practices in contemporary Africa. "Sacred words" are taken to mean holy texts as in divination, the Bible and the Quran. Toyin Falola evaluates how religious leaders engage with sacred words, both orals and texts, engendering practices that reveal the expression of religious beliefs, the impact of those beliefs, and the knowledge contained in them. Attention is given to the key ideas in the words chosen by religious leaders, and how they form a continuous knowledge system, impacting the politics of managing society and people."--